UN accountability mandates in international justice - D'Alessandra, F (Oxford University Press, 2023)
This article discusses recent developments within the international justice field, specifically the establishment of a new generation of ‘UN accountability mandates’ aimed to fill important impunity gaps. Generally tasked to ‘collate, collect, analyse, and preserve evidence’ of international crimes, and make it available to support accountability proceedings, these mandates exist along a spectrum based on both the strength of their requirements and their operational set up. Some of these mandates – and particularly the investigative mechanisms created for Syria, Myanmar and for Daesh/ISIL – are specifically tasked to fulfil pre-prosecutorial functions – i.e., build case files to support criminal proceedings – and enjoy far greater resources and independence. Other mandates are more ‘hybrid’ (i.e., expected to fulfil both the role of a traditional human rights inquiry, but with ‘add on’ requirements to also support judicial accountability, including criminal), although enjoying far less resources. All, however, play a crucial role within the broader international justice ‘ecosystem’ and share common challenges – which this article submits would be best addressed by permanently centralising certain support functions under a single entity. The article will first provide an overview of how and why such UN accountability mandates have evolved over the last decade, of the important role that such mandates have come to play and of the current state of affairs. It will then turn to discussing the case and proposed models for a permanent UN investigative mandate to be stood up on a permanent basis. After providing a comparative analysis of the possible alternatives, the article will conclude with the author’s recommendations and ideas moving forward.